Analysis of terminal structures of RNA from potato virus X. - Sonenberg, N (1978)
The 5'-end structure of potato virus X RNA was determined following enzymatic methylation in vitro. A single 3H-methyl group was introduced into the 2'-position of the 5'-penultimate residue and the end structure was determined as m7GpppG(m)pAp(Xp)3G. This part of the RNA apparently is involved in binding to ribosomes since it can be partially protected against RNase digestion by wheat germ 40S ribosomes. PVX RNA was not retained by poly(U)-sepharose, indicating that it does not contain a 3'-terminal poly(A) tract.